The relationship between physical activity and short video addiction among college students: mediating effects of self-control and social anxiety - Wang, Guoyu; Wu, Kunbo; Gu, Jiajie; Zhang, Zheng (Frontiers in Psychology, 2025)
IntroductionShort video addiction has significantly altered college students’ learning, living, and entertainment habits, exerting a negative impact on their physical and mental health, which has drawn widespread attention from scholars.MethodsThis study surveyed 650 college students using the Physical Activity Level Scale, Self-Control Scale, Adolescent Social Anxiety Scale, and Short Video Addiction Scale through the convenient sampling method to explore the mechanism of physical activity’s impact on short video addiction.ResultsThe results of the study indicate that: (1) physical activity has a significant and negative impact on short video addiction; (2) physical activity influences short video addiction through the mediating effect of self-control; (3) physical activity influences short video addiction through the mediating effect of social anxiety; (4) self-control and social anxiety play a chain mediating role in the impact of physical activity on short video addiction.ConclusionThese findings help researchers and educators better understand the underlying mechanisms of the relationship between physical activity and short video addiction, and provide practical and effective operational recommendations for the prevention and intervention of short video addiction among college students.